Sagger for solid-phase sintering of positive electrode of high-nickel NCA ternary lithium battery and preparation method of sagger
Through the new preparation method, using in-situ silicon thermal reaction and spray-granulation-drying technology, combining the skeleton structure of magnesium-aluminum spinel and mullite, a high-temperature and high-thermal conduction phase that is resistant to oxidation and erosion are solved, and high nickel is solved The sintering temperature control of the sintering bowl for the solid phase sintering of NCA ternary lithium battery and the problem of easy shedding of the composite layer, achieving efficient squeezing bowl preparation and excellent service performance.
Patent Information
- Application Number
- CN202411615212.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
In the prior art, the research and development and industrial application of the silo for the positive electrode of high-nickel NCA ternary lithium battery are relatively lacking, and there are problems such as difficulty in controlling the silo temperature and easy to fall off the composite layer, which affects the integrity and service life of the silo. .
A new preparation method is adopted, through in-situ silicon thermal reaction and spray-granulation-drying integrated technology, combining the skeleton structure and dense network accumulation of magnesium-aluminum spinel particles and mullite fine powder, and cerium oxide fine powder. The high-temperature solid solution and non-wetting properties of the powder form high-temperature and high-thermal conduction phases that are oxidized and eroded, avoiding the use of composite layers.
It has achieved good integrity, high yield, excellent sintering performance and high thermal shock stability for the silencing of high-nickel NCA ternary lithium battery positive electrode, strong permeability of high-nickel NCA ternary lithium battery positive electrode materials. It significantly improves the service life of the samurai.
Smart Images

Figure CN119462123A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of saggers, and in particular to a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode and a preparation method thereof. Background Art
[0002] Ternary lithium batteries have been widely used in the field of power batteries due to their high energy density, good cycle performance and large capacity. Li Qin, Liang Wenying. Research progress on composite modification of ternary cathode materials[J]. New Chemical Industry Materials, 2024, 52(z1): 1-4 Ternary lithium batteries mainly include nickel cobalt aluminum oxide (NCA) and nickel cobalt manganese oxide (NCM). They are a type of lithium-ion battery with nickel and cobalt as the main elements and manganese salts or aluminum salts to stabilize the chemical structure ( Qin Cunpeng , Liu Jiayi, Tan Xiaohua, et al. 0.8 Co 0.15 Al 0.05 Research progress on oxide coating modification of O2(NCA) ternary cathode materials[J]. Chi Industry, 2019, 23(6): 327-334 ), but there are significant differences between the two:
[0003] (1) NCA has a higher energy density than NCM. In the ternary system, aluminum doping can improve the chemical stability of battery cycles ( Zhang Busheng, Wu Yongqian, Zhang Ke, et al. Research progress of nickel-cobalt-aluminum ternary cathode materials [J]. Guangzhou Chemical Industry, 2017, 45(11): 3-5 ), so NCA has good cycle charge and discharge performance.
[0004] (2) The aluminum element in the NCA ternary is more likely to stabilize the high-nickel system and form an aluminum-nickel spinel solid solution. Therefore, the NCA ternary system has a higher energy density ( Yan Xiaocen, Du Chengting, Ding Jiaqi, et al. Ternary cathode materials LiNi 0.8 Co 0.15 Al 0.05 Research progress of O2 preparation methods[J]. New Chemical Materials, 2024, 52(6): 44-49 ).
[0005] (3) The preparation process requirements of NCA ternary positive electrode materials are higher. Although aluminum is abundant and the cost of alumina is low, the characteristics of Al2O3 (including Al(OH)3) that it is easy to react with both acid and alkali make the preparation process requirements of NCA more complicated. In addition, unlike the air atmosphere used for solid-phase sintering of NCM ternary positive electrode, NCA ternary positive electrode solid-phase sintering uses oxygen-rich or full oxygen sintering. This is to promote the full oxidation of nickel elements in the raw material components, and the sintering temperature control of NCA ternary positive electrode is more stringent. If the sintering temperature is too low, nickel elements are difficult to convert into a high-valent state (+3 valence) and are stable. If the sintering temperature is too high, it will decompose back into a low-valent state (+2 valence).
[0006] In general, due to the change of aluminum doping characteristics in NCA ternary system, many process factors such as sintering heat treatment temperature, grain growth and development, and surface coating of NCA have undergone significant changes, which has led to the typical difference between NCA solid phase sintering saggers and NCM heat treatment saggers. In particular, domestic ternary cathodes are dominated by NCM, which has also affected the research and development of NCA solid phase sintering saggers to a certain extent. There is almost no mature application of high-nickel NCA ternary cathode solid phase sintering saggers.
[0007] At present, the development and industrial application of saggers for solid-phase sintering of high-nickel NCA ternary lithium battery positive electrode in China mainly continue the idea of high-nickel NCM ternary lithium battery positive electrode, or draw on the scheme of special saggers for sintering positive electrode materials such as lithium cobalt oxide, lithium iron phosphate, and lithium manganese oxide. Most of them use cordierite, mullite, corundum or spinel as the main raw materials, and add zirconium-containing components, non-oxide components, etc. ( A long-life ternary positive electrode material firing sagger and preparation process, CN202311744260.5 ), after optimizing the ratio, mixing, trapping, molding, and then drying and firing to obtain the finished sagger. On the one hand, as mentioned above, the different characteristics of the incorporation of manganese / aluminum elements lead to obvious differences in the erosion and damage of the sagger. The service life of the sagger used for NCM heat treatment is as high as more than 40 times, while the service life of the sagger used for NCA solid phase sintering is only 4 to 8 times; on the other hand, the production process and raw materials of NCA and NCM or other positive electrode materials are also different, so the influence of the sagger on the quality of high-nickel ternary positive electrode materials is significantly different. In addition, most of the special saggers for heat treatment of NCM high-nickel ternary positive electrodes use composite layer technology-compounding a coating material with good corrosion resistance on the inner wall (bottom and side wall) of the sagger, but during the sagger cycle service process, the composite layer is easy to fall off and enter the lithium battery positive electrode material, which will also seriously affect the quality and performance of the positive electrode material. Summary of the invention
[0008] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to propose a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode and a preparation method thereof. The method has a simple process and does not require a composite layer or other coating. The prepared sagger has good integrity, a high yield, excellent sintering performance, high thermal shock stability, and strong resistance to erosion and permeability of high-nickel NCA ternary lithium battery positive electrode materials.
[0009] The present invention provides a method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode, comprising the following steps:
[0010] S1. Grind bauxite powder, active Al2O3 powder, pyrophyllite powder, Si powder and boric acid in a mass ratio of 100:(20-30):(40-60):(5-8):(3-6) to a particle size of ≤100 μm to obtain a mixed powder;
[0011] S2, adding silica sol accounting for 12-15% of the mass of the mixed powder to the mixed powder and stirring to obtain a slurry;
[0012] S3, spraying and granulating the slurry to obtain microspheres;
[0013] S4, the microsphere material is kept at 1180-1220° C. for 6-8 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and then passed through a 250-mesh round hole sieve, and the sieve material is taken to obtain a fired microsphere material;
[0014] S5. Mixing magnesium aluminum spinel particles, mullite fine powder, sintered microspheres, talc fine powder and cerium oxide fine powder in a mass ratio of 100:(10-12):(55-60):(5-8):(2-4) to obtain a mixture;
[0015] S6, adding pulp waste liquid accounting for 3.5-4.5% of the mass of the mixed material to the mixed material, and sealing the mixed material after mixing to obtain aged material;
[0016] S7, pressing the aged material into a shape, drying it and keeping it at 1360-1420° C. for 3-4 hours, and cooling it to room temperature with the furnace to obtain a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode.
[0017] Furthermore, the pH value of the silica sol is 9-10; the solid content of the silica sol is 30-35%; and the particle size of the silica sol is 25-70 nm.
[0018] Furthermore, the particle size of the magnesium-aluminum spinel particles is 0.1 to 2.5 mm, wherein the mass ratio of [0.1 mm to 0.5 mm] particles, [1.0 mm to 1.5 mm] particles and [2.0 mm to 2.5 mm] particles is (20 to 30): (25 to 30): (25 to 35); the SiO2 content of the magnesium-aluminum spinel particles is ≤0.1 wt%.
[0019] Furthermore, the particle size of the mullite fine powder is 40 to 100 μm, wherein the mass ratio of [40 μm to 50 μm] fine powder, [50 μm to 80 μm] fine powder and [80 μm to 100 μm] fine powder is (10 to 15): (30 to 35): (45 to 55); the Fe2O3 content of the mullite fine powder is ≤0.1wt%, and the TiO2 content is ≤0.2wt%.
[0020] Furthermore, the particle size of the talc fine powder is ≤80 μm; and the particle size of the cerium oxide fine powder is ≤40 μm.
[0021] Furthermore, in step S3, the slurry is dried in a spray granulator at 180-220° C. for 30-40 seconds to obtain microspheres.
[0022] Furthermore, the pH value of the pulp waste liquid is 6.5-7.0.
[0023] Furthermore, in step S6, the mixture is mixed for 5 to 8 minutes, and the material is sealed for 4 to 5 hours.
[0024] Furthermore, in step S7, the aged material is pressed into shape at 60-80 MPa and dried at 25-35° C. for 10-12 hours.
[0025] A sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode prepared by the above-mentioned preparation method.
[0026] The beneficial effects of the present invention are:
[0027] (1) The present invention starts from the matrix part of the sagger composition, through in-situ silicon thermal reaction, using the liquid medium environment created by boric acid at high temperature, and combining the decomposition and nitridation of bauxite and pyrophyllite, to form flaky SiAlON and layered BN and other high-temperature and high-thermal conductive phases that are resistant to oxidation and corrosion, thereby improving the anti-penetration performance and thermal shock stability of the sagger against lithium nickel components.
[0028] (2) The present invention utilizes the integrated spray-granulation-drying technology to shape the matrix material, and sieves it after high-temperature sintering, thereby improving the sphericity and regularity of the matrix material, which is beneficial to improving the dispersibility of the synthetic matrix material and maintaining the integrity of the synthetic matrix material, and significantly improving the service performance of the sagger components under high-temperature oxygen-rich or pure oxygen conditions.
[0029] (3) The present invention forms a skeleton through the discrete distribution of magnesium-aluminum spinel particle aggregate, and utilizes the continuous filling of synthetic matrix material and mullite fine powder to construct a densified network stacking of the sagger, and forms eucryptite / spodumene through the corrosion reaction of mullite and high-nickel NCA ternary lithium battery positive electrode material (during service), thereby reducing the thermal expansion of the matrix part of the sagger, and further improving the corrosion resistance and service life of the sagger.
[0030] (4) The present invention utilizes the high-temperature solid solution of cerium oxide and magnesium aluminum spinel to increase the melting point of the spinel-mullite grain boundary phase, and forms grain boundary pinning through the non-wetting characteristics of cerium oxide fine powder, thereby hindering the wetting and penetration of the high-nickel NCA ternary lithium battery positive electrode into the sagger, thereby avoiding the adhesion and penetration of the positive electrode material into the sagger.
[0031] (5) The present invention does not need to adopt composite layer or composite coating technology, and utilizes overall mixing and dispersion and one-step pressing molding technology to prepare a homogeneous sagger, thereby avoiding the peeling of the composite layer or coating, further ensuring the quality of the high-nickel NCA ternary lithium battery positive electrode material, and also improving the yield rate of the sagger.
[0032] The sagger for solid phase sintering of high nickel NCA ternary lithium battery positive electrode prepared by the present invention is tested:
[0033] Finished product rate 99.3-99.7%; apparent porosity 12-15% (GB / T2997-2015);
[0034] Flexural strength: 18-24MPa (GB / T3001-2017); 1100℃ circulating water cooling 5 times thermal shock stability test (GB / T30873-2014) residual flexural strength retention rate is 97-98%, 1100℃×30h alkali resistance test (GB / T14983-2008) strength change rate is 1.8-2.2%.
[0035] Therefore, the process of the present invention is simple, and the prepared sagger has good integrity, high yield, excellent sintering performance, high thermal shock stability, and strong resistance to corrosion and permeability of high-nickel NCA ternary lithium battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a SEM photograph of the sagger sample for solid-phase sintering of the high-nickel NCA ternary lithium battery positive electrode prepared in Example 1.
[0037] Figure 2 This is a SEM photograph of the sagger sample for solid-phase sintering of the high-nickel NCA ternary lithium battery positive electrode prepared in Example 1 after corrosion. DETAILED DESCRIPTION
[0038] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0039] Example 1
[0040] A method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode, the specific steps are as follows:
[0041] S1. Add bauxite fine powder, active Al2O3 fine powder, pyrophyllite fine powder, Si powder and boric acid into a high-energy ball mill in a mass ratio of 100:20:60:8:5 and mix and grind to a particle size of ≤100 μm to obtain a mixed powder;
[0042] S2, adding silica sol accounting for 14% of the mass of the mixed powder to the mixed powder, stirring for 5 to 6 minutes to obtain a slurry;
[0043] S3, putting the slurry into a spray granulator, and drying it at 210° C. for 40 seconds to obtain microspheres;
[0044] S4, placing the microsphere material in a resistance furnace, in a nitrogen atmosphere, and keeping it at 1210° C. for 8 hours, cooling it to room temperature with the furnace, and then passing it through a 250-mesh round hole sieve, taking the material under the sieve to obtain the fired microsphere material;
[0045] S5, adding magnesium aluminum spinel particles, mullite fine powder, sintered microspheres, talc fine powder and cerium oxide fine powder into a planetary ball mill at a mass ratio of 100:10:55:5:4, and mixing for 15 to 20 minutes to obtain a mixture;
[0046] S6, adding 4.2% of the mass of the pulp waste liquid to the mixture, mixing for 5 to 8 minutes, sealing the mixture for 4 to 5 hours, and obtaining an aged material;
[0047] S7. Press the aged material into shape at 60-80 MPa, dry it at 25-35° C. for 10-12 h, place it in a high-temperature furnace, keep it at 1380° C. for 3 h, and cool it to room temperature with the furnace to obtain a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode.
[0048] The pH value of the silica sol is 9; the solid content of the silica sol is 33%; and the particle size of the silica sol is 25 to 70 nm.
[0049] The particle size of the magnesium-aluminum spinel particles is 0.1-2.5 mm, wherein the mass ratio of [0.1 mm-0.5 mm] particles, [1.0 mm-1.5 mm] particles and [2.0 mm-2.5 mm] particles is 28:25:32; the SiO2 content of the magnesium-aluminum spinel particles is ≤0.1 wt%.
[0050] The particle size of the mullite fine powder is 40-100 μm, wherein the mass ratio of [40 μm-50 μm] fine powder, [50 μm-80 μm] fine powder and [80 μm-100 μm] fine powder is 10:34:55; the Fe2O3 content of the mullite fine powder is ≤0.1wt%, and the TiO2 content is ≤0.2wt%.
[0051] The particle size of talc fine powder is ≤80μm.
[0052] The particle size of the cerium oxide fine powder is ≤40 μm.
[0053] The pH value of pulp waste liquid is 6.5-7.0.
[0054] Figure 1 This is a SEM photo of a sagger sample for solid phase sintering of a high nickel NCA ternary lithium battery positive electrode. Figure 1 It can be seen that the particles are tightly bonded to the matrix material without obvious boundaries. The white bright spots of cerium oxide are solid-dissolved and embedded between the spinel particles and the matrix. The sample has excellent overall bonding and high density.
[0055] Figure 2 This is a SEM photo of the corroded sagger sample used for solid-phase sintering of high-nickel NCA ternary lithium battery positive electrode. Figure 2It can be seen that after the corrosion reaction, the cerium oxide that was originally solid-dissolved and embedded between the particles and the matrix is in a "leached state" and is continuously distributed between the matrices. The sample connection is tighter. This is mainly because the high-nickel NCA ternary positive electrode material reacts with the sagger body to form a low-expansion phase that fills between the particles. The sample maintains strong integrity. Although a small amount of corrosion cracks can be found, the sample has no cracking, shedding or stratification, indicating that the sagger sample has good corrosion resistance and permeability properties.
[0056] The sagger for solid phase sintering of high nickel NCA ternary lithium battery positive electrode prepared in this embodiment was tested:
[0057] Finished product rate: 99.5%; apparent porosity: 12% (GB / T2997-2015);
[0058] Flexural strength: 20MPa (GB / T3001-2017); 1100℃ circulating water cooling 5 times thermal shock stability test (GB / T30873-2014) residual flexural strength retention rate is 98%, 1100℃×30h alkali resistance test (GB / T14983-2008) strength change rate is 2.0%.
[0059] Example 2
[0060] A method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode, the specific steps are as follows:
[0061] S1. Add bauxite powder, active Al2O3 powder, pyrophyllite powder, Si powder and boric acid into a high-energy ball mill in a mass ratio of 100:28:45:5:6 and mix and grind to a particle size of ≤100 μm to obtain a mixed powder;
[0062] S2, adding silica sol accounting for 15% of the mass of the mixed powder to the mixed powder, stirring for 5 to 6 minutes to obtain a slurry;
[0063] S3, putting the slurry into a spray granulator, and drying it at 200° C. for 35 seconds to obtain microspheres;
[0064] S4, placing the microsphere material in a resistance furnace, in a nitrogen atmosphere, and keeping it at 1220° C. for 7 hours, cooling it to room temperature with the furnace, and then passing it through a 250-mesh round hole sieve, taking the material under the sieve to obtain the fired microsphere material;
[0065] S5, adding magnesium aluminum spinel particles, mullite fine powder, sintered microspheres, talc fine powder and cerium oxide fine powder into a planetary ball mill at a mass ratio of 100:12:60:6:4, and mixing for 15 to 20 minutes to obtain a mixture;
[0066] S6, adding 4.0% of the pulp waste liquid by weight of the mixture to the mixture, mixing for 5 to 8 minutes, and sealing the mixture for 4 to 5 hours to obtain an aged material;
[0067] S7. Press the aged material into shape at 60-80 MPa, dry it at 25-35° C. for 10-12 h, place it in a high-temperature furnace, keep it at 1420° C. for 3 h, and cool it to room temperature with the furnace to obtain a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode.
[0068] The pH value of the silica sol is 10; the solid content of the silica sol is 35%; and the particle size of the silica sol is 25-70 nm.
[0069] The particle size of the magnesium-aluminum spinel particles is 0.1-2.5 mm, wherein the mass ratio of [0.1 mm-0.5 mm] particles, [1.0 mm-1.5 mm] particles and [2.0 mm-2.5 mm] particles is 25:30:26; the SiO2 content of the magnesium-aluminum spinel particles is ≤0.1 wt%.
[0070] The particle size of the mullite fine powder is 40-100 μm, wherein the mass ratio of [40 μm-50 μm] fine powder, [50 μm-80 μm] fine powder and [80 μm-100 μm] fine powder is 12:30:45; the Fe2O3 content of the mullite fine powder is ≤0.1wt%, and the TiO2 content is ≤0.2wt%.
[0071] The particle size of talc fine powder is ≤80μm.
[0072] The particle size of the cerium oxide fine powder is ≤40 μm.
[0073] The pH value of pulp waste liquid is 6.5-7.0.
[0074] The sagger for solid phase sintering of high nickel NCA ternary lithium battery positive electrode prepared in this embodiment was tested:
[0075] Finished product rate: 99.3%; apparent porosity: 13% (GB / T2997-2015);
[0076] Flexural strength: 22MPa (GB / T3001-2017); 1100℃ circulating water cooling 5 times thermal shock stability test (GB / T30873-2014) residual flexural strength retention rate is 97%, 1100℃×30h alkaline resistance test (GB / T14983-2008) strength change rate is 2.2%.
[0077] Example 3
[0078] A method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode, the specific steps are as follows:
[0079] S1. Add bauxite fine powder, active Al2O3 fine powder, pyrophyllite fine powder, Si powder and boric acid into a high-energy ball mill in a mass ratio of 100:30:50:7:3 and mix and grind to a particle size of ≤100 μm to obtain a mixed powder;
[0080] S2, adding silica sol accounting for 12% of the mass of the mixed powder to the mixed powder, stirring for 5 to 6 minutes to obtain a slurry;
[0081] S3, putting the slurry into a spray granulator, and drying at 180° C. for 30 seconds to obtain microspheres;
[0082] S4, placing the microsphere material in a resistance furnace, in a nitrogen atmosphere, and keeping it at 1180° C. for 6 hours, cooling it to room temperature with the furnace, and then passing it through a 250-mesh round hole sieve, taking the material under the sieve to obtain the fired microsphere material;
[0083] S5, adding magnesium aluminum spinel particles, mullite fine powder, sintered microspheres, talc fine powder and cerium oxide fine powder into a planetary ball mill at a mass ratio of 100:10:56:7:3, and mixing for 15 to 20 minutes to obtain a mixture;
[0084] S6, adding 4.5% of the mass of the pulp waste liquid to the mixture, mixing for 5 to 8 minutes, sealing the mixture for 4 to 5 hours, and obtaining an aged material;
[0085] S7. Press the aged material into shape at 60-80 MPa, dry it at 25-35° C. for 10-12 hours, place it in a high-temperature furnace, keep it at 1360° C. for 4 hours, and cool it to room temperature with the furnace to obtain a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode.
[0086] The pH value of the silica sol is 9; the solid content of the silica sol is 30%; and the particle size of the silica sol is 25-70 nm.
[0087] The particle size of the magnesium-aluminum spinel particles is 0.1-2.5 mm, wherein the mass ratio of [0.1 mm-0.5 mm] particles, [1.0 mm-1.5 mm] particles and [2.0 mm-2.5 mm] particles is 30:26:35; the SiO2 content of the magnesium-aluminum spinel particles is ≤0.1 wt%.
[0088] The particle size of the mullite fine powder is 40-100 μm, wherein the mass ratio of [40 μm-50 μm] fine powder, [50 μm-80 μm] fine powder and [80 μm-100 μm] fine powder is 15:35:50; the Fe2O3 content of the mullite fine powder is ≤0.1wt%, and the TiO2 content is ≤0.2wt%.
[0089] The particle size of talc fine powder is ≤80μm.
[0090] The particle size of the cerium oxide fine powder is ≤40 μm.
[0091] The pH value of pulp waste liquid is 6.5-7.0.
[0092] The sagger for solid phase sintering of high nickel NCA ternary lithium battery positive electrode prepared in this embodiment was tested:
[0093] Finished product rate: 99.7%; apparent porosity: 15% (GB / T2997-2015);
[0094] Flexural strength: 24MPa (GB / T3001-2017); 1100℃ circulating water cooling 5 times thermal shock stability test (GB / T30873-2014) residual flexural strength retention rate is 97.2%, 1100℃×30h alkaline resistance test (GB / T14983-2008) strength change rate is 2.1%.
[0095] Example 4
[0096] A method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode, the specific steps are as follows:
[0097] S1. Add bauxite fine powder, active Al2O3 fine powder, pyrophyllite fine powder, Si powder and boric acid into a high-energy ball mill in a mass ratio of 100:25:40:6:4 and mix and grind to a particle size of ≤100 μm to obtain a mixed powder;
[0098] S2, adding silica sol accounting for 13% of the mass of the mixed powder to the mixed powder, stirring for 5 to 6 minutes to obtain a slurry;
[0099] S3, putting the slurry into a spray granulator, and drying at 220° C. for 30 seconds to obtain microspheres;
[0100] S4, placing the microsphere material in a resistance furnace, in a nitrogen atmosphere, and keeping it at 1200° C. for 6 hours, cooling it to room temperature with the furnace, and then passing it through a 250-mesh round hole sieve, taking the material under the sieve to obtain the fired microsphere material;
[0101] S5, adding magnesium aluminum spinel particles, mullite fine powder, sintered microspheres, talc fine powder and cerium oxide fine powder into a planetary ball mill at a mass ratio of 100:11:58:8:2, and mixing for 15 to 20 minutes to obtain a mixture;
[0102] S6, adding pulp waste liquid accounting for 3.5% of the mass of the mixed material to the mixed material, mixing for 5 to 8 minutes, sealing the mixed material for 4 to 5 hours, and obtaining an aged material;
[0103] S7. Press the aged material into shape at 60-80 MPa, dry it at 25-35° C. for 10-12 hours, place it in a high-temperature furnace, keep it at 1400° C. for 4 hours, and cool it to room temperature with the furnace to obtain a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode.
[0104] The pH value of the silica sol is 10; the solid content of the silica sol is 32%; and the particle size of the silica sol is 25 to 70 nm.
[0105] The particle size of the magnesium-aluminum spinel particles is 0.1-2.5 mm, wherein the mass ratio of [0.1 mm-0.5 mm] particles, [1.0 mm-1.5 mm] particles and [2.0 mm-2.5 mm] particles is 20:28:25; the SiO2 content of the magnesium-aluminum spinel particles is ≤0.1 wt%.
[0106] The particle size of the mullite fine powder is 40-100 μm, wherein the mass ratio of [40 μm-50 μm] fine powder, [50 μm-80 μm] fine powder and [80 μm-100 μm] fine powder is 13:32:52; the Fe2O3 content of the mullite fine powder is ≤0.1wt%, and the TiO2 content is ≤0.2wt%.
[0107] The particle size of talc fine powder is ≤80μm.
[0108] The particle size of the cerium oxide fine powder is ≤40 μm.
[0109] The pH value of pulp waste liquid is 6.5-7.0.
[0110] The sagger for solid phase sintering of high nickel NCA ternary lithium battery positive electrode prepared in this embodiment was tested:
[0111] Finished product rate: 99.6%; apparent porosity: 15% (GB / T2997-2015);
[0112] Flexural strength: 18MPa (GB / T3001-2017); 1100℃ circulating water cooling 5 times thermal shock stability test (GB / T30873-2014) residual flexural strength retention rate is 97.6%, 1100℃×30h alkaline resistance test (GB / T14983-2008) strength change rate is 1.8%.
[0113] For matters not mentioned above, the prior art applies.
[0114] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode, characterized in that: The steps include: S1. Grind bauxite powder, active Al2O3 powder, pyrophyllite powder, Si powder and boric acid in a mass ratio of 100:(20-30):(40-60):(5-8):(3-6) to a particle size of ≤100 μm to obtain a mixed powder; S2, adding silica sol accounting for 12-15% of the mass of the mixed powder to the mixed powder and stirring to obtain a slurry; S3, spraying and granulating the slurry to obtain microspheres; S4, the microsphere material is kept at 1180-1220° C. for 6-8 hours under a nitrogen atmosphere, cooled to room temperature with the furnace, and then passed through a 250-mesh round hole sieve, and the sieve material is taken to obtain a fired microsphere material; S5. Mixing magnesium aluminum spinel particles, mullite fine powder, sintered microspheres, talc fine powder and cerium oxide fine powder in a mass ratio of 100:(10-12):(55-60):(5-8):(2-4) to obtain a mixture; S6, adding pulp waste liquid accounting for 3.5-4.5% of the mass of the mixed material to the mixed material, and sealing the mixed material after mixing to obtain aged material; S7, pressing the aged material into a shape, drying it and keeping it at 1360-1420° C. for 3-4 hours, and cooling it to room temperature with the furnace to obtain a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode.
2. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: The pH value of the silica sol is 9-10; the solid content of the silica sol is 30-35%; and the particle size of the silica sol is 25-70nm.
3. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: The particle size of the magnesium-aluminum spinel particles is 0.1-2.5 mm, wherein the mass ratio of [0.1 mm-0.5 mm] particles, [1.0 mm-1.5 mm] particles and [2.0 mm-2.5 mm] particles is (20-30):(25-30):(25-35); the SiO2 content of the magnesium-aluminum spinel particles is ≤0.1 wt%.
4. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: The particle size of the mullite fine powder is 40-100 μm, wherein the mass ratio of [40 μm-50 μm] fine powder, [50 μm-80 μm] fine powder and [80 μm-100 μm] fine powder is (10-15): (30-35): (45-55); the Fe2O3 content of the mullite fine powder is ≤0.1wt%, and the TiO2 content is ≤0.2wt%.
5. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode as claimed in claim 1, characterized in that: The particle size of the talc fine powder is ≤80 μm; the particle size of the cerium oxide fine powder is ≤40 μm.
6. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: In step S3, the slurry is put into a spray granulator and dried at 180-220° C. for 30-40 seconds to obtain microspheres.
7. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: The pH value of the pulp waste liquid is 6.5-7.
0.
8. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: In step S6, the mixture is mixed for 5 to 8 minutes, and the mixture is sealed for 4 to 5 hours.
9. The method for preparing a sagger for solid-phase sintering of a high-nickel NCA ternary lithium battery positive electrode according to claim 1, characterized in that: In step S7, the aged material is pressed into shape at 60-80 MPa and dried at 25-35° C. for 10-12 hours.
10. A sagger for solid-phase sintering of a high-nickel NCA ternary positive electrode prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Magnesium-aluminum spinel-BN-Sialon multiphase refractory raw material and preparation method thereof
CN104761271A
A low-cost long-service-lifetime ceramic saggar and a preparing method thereof
CN106946553A
Silicon carbide-magnesium aluminum spinel composite refractory material
CN107879753A
Alkaline powder kiln furniture with controlled porosity coating
CN118475547A
Manufacture of sialon sintered body
JP1986141671A